PERANCANGAN APLIKASI PENENTUAN KUALITAS KELAPA MENGGUNAKAN METODE WEIGHTED PRODUCT (WP) BERBASIS WEB - Sulasih Wijayanti (Selodang Mayang: Jurnal Ilmiah Badan Perencanaan Pembangunan Daerah Kabupaten Indragiri Hilir, 2020)
Plantation is one of the backbone of economy, Indragiri Hilir (Inhil), Riau. One of them is coconut, with the big potential of coconut, Indragiri Hilir made the coconut palm as superior product. Sometimes, there is lack of knowledge and information about the coconut quality. This research aimed to apply the weighted product (WP), an application of selecting the coconut quality, which can solve the problem for coconut seller in order to get the information. Therefore, in order to know the price and quality of coconut by using the weighted product (WP) method, it has to use multiplication to connect attribute value, where the value must be raised first with the weight of the attribute in question. By using the weighted product (WP) method of decision support, then implemented into a system that determines the level of importance in each criteria, they are; price and weight. The source of knowledge system is obtained by collecting data and information. This software is expected to help to determine the quality of coconut to the buyer of coconut and farmer.